2016
DOI: 10.1200/jco.2015.64.8162
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Racial Disparities in Early Supportive Medication Use and End-of-Life Care Among Medicare Beneficiaries With Stage IV Breast Cancer

Abstract: Early supportive care may improve quality of life and end-of-life care among patients with cancer. We assessed racial disparities in early use of medications for common cancer symptoms (depression, anxiety, insomnia) and whether these potential disparities modify end-of-life care. MethodsWe used 2007 to 2012 SEER-Medicare data to evaluate use of supportive medications (opioid pain medications and nonopioid psychotropics, including antidepressants/anxiolytics and sleep aids) in the 90 days postdiagnosis among b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…In addition to underuse of services, disparities also exist with overuse of treatment in the EOL setting. Compared to elderly white women, elderly black women with MBC are more likely to die in the hospital, and be admitted to the ICU, hospital, or ED within the last month of life [34]. These results are also similar to our own results which found that elderly black women with MBC were more likely to utilize aggressive EOL care compared to elderly white women with MBC.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition to underuse of services, disparities also exist with overuse of treatment in the EOL setting. Compared to elderly white women, elderly black women with MBC are more likely to die in the hospital, and be admitted to the ICU, hospital, or ED within the last month of life [34]. These results are also similar to our own results which found that elderly black women with MBC were more likely to utilize aggressive EOL care compared to elderly white women with MBC.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research has shown significant racial/ethnic disparities related to adequacy of pain and symptom control, and perceived unmet needs for supportive services [31–34]. In addition, other studies have found that among patients with MBC at the EOL, elderly black women were less likely to utilize hospice [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps most compelling among the negative findings is race, which previously has been correlated with increased receipt of aggressive interventions and intensive care use at the EOL in adult patients with cancer . A previous study conducted at this institution 8 years ago likewise showed that race did not affect EOL care planning or resuscitation status for children with cancer, but that study did not query potential disparities related to location of death .…”
Section: Discussionmentioning
confidence: 93%
“…Especially, recent studies of novel but costly cancer drugs reported that racial minority patients were less likely to use those drugs than non-minority patients [9, 10]. Prior work documented racial variation in receipt of traditional interferon-based HCV treatments, with lower rates of utilization for Blacks than for Whites, but medical factors explained some of that difference [10].…”
Section: Introductionmentioning
confidence: 99%